Investment Risk Management Strategies in Sukuk: A Sharia Management Perspective - Mahadewi, Erlina Puspitaloka (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
Sukuk, as a Sharia-compliant financial instrument, has gained increasing popularity among global investors. However, as the market evolves, challenges related to risk management in compliance with Sharia principles have also emerged. This paper aims to explore investment risk management strategies in sukuk from a Sharia management perspective. Using qualitative analysis and literature review methods, the study highlights the importance of applying Sharia principles in identifying and managing risks, including market risk, liquidity risk, and default risk. Sharia-compliant risk mitigation strategies, such as portfolio diversification, sukuk performance monitoring, and the use of Sharia contracts like wakalah and mudharabah, are discussed in depth. Additionally, the paper emphasizes the role of Sharia supervisory authorities in ensuring that sukuk instruments remain compliant with Islamic law, providing added security for investors. The findings of this study offer valuable insights for investors, financial institutions, and policymakers in developing effective and Sharia-compliant risk management frameworks.